Examining the relationship between use of sexually explicit media and sexual risk behavior in a sample of men who have sex with men in Norway. Issue 3 (16th February 2015) - Træen, Bente; Noor, Syed W.; Hald, Gert Martin; Rosser, B. R. Simon; Brady, Sonya S.; Erickson, Darin; Galos, Dylan L.; Grey, Jeremy A.; Horvath, Keith J.; Iantaffi, Alex; Kilian, Gudruna; Wilkerson, J. Michael
<x xml:space="preserve">Abstract</x> The purpose of this study was to investigate consumption patterns of gay‐oriented sexually explicit media (SEM) among men who have sex with men (MSM) in Norway, with a particular emphasis on a possible relationship between gay SEM consumption and HIV risk behavior. Participants included 529 MSM living in Norway recruited online to complete a SEM consumption and sexual risk survey. Of the 507 participants who responded to the all items measuring exposure to SEM, 19% reported unprotected anal intercourse with a casual partner (UAI) in last 90 days, and 14% reported having had sero‐discordant UAI. Among those with UAI experience, 23% reported receptive anal intercourse (R‐UAI) and 37% reported insertive anal intercourse (I‐UAI). SEM consumption was found to be significantly associated with sexual risk behaviors. Participants with increased consumption of bareback SEM reported higher odds of UAI and I‐UAI after adjusting for other factors using multivariable statistics. MSM who started using SEM at a later age reported lower odds of UAI and I‐UAI than MSM who started earlier. Future research should aim at understanding how MSM develop and maintain SEM preferences and the relationship between developmental and maintenance factors and HIV sexual risk behavior.